2014
DOI: 10.1186/preaccept-7219692771243941
|View full text |Cite
|
Sign up to set email alerts
|

Branchial NH

Abstract: Background: Cephalopods have evolved strong acid-base regulatory abilities to cope with CO 2 induced pH fluctuations in their extracellular compartments to protect gas transport via highly pH sensitive hemocyanins. To date, the mechanistic basis of branchial acid-base regulation in cephalopods is still poorly understood, and associated energetic limitations may represent a critical factor in high power squids during prolonged exposure to seawater acidification. Results: The present work used adult squid Sepiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Many of the previous studies of OA and squid showed repeated significant effects on an array of variables (Lacoue-Labarthe et al 2011;Kaplan et al 2013;Hu et al 2014;Rosa et al 2014a;Navarro et al 2016). Here, we had trials that were affected by relatively high levels of pCO 2 and low pH t , but also trials that were not.…”
Section: A Broader Squid Contextmentioning
confidence: 99%
“…Many of the previous studies of OA and squid showed repeated significant effects on an array of variables (Lacoue-Labarthe et al 2011;Kaplan et al 2013;Hu et al 2014;Rosa et al 2014a;Navarro et al 2016). Here, we had trials that were affected by relatively high levels of pCO 2 and low pH t , but also trials that were not.…”
Section: A Broader Squid Contextmentioning
confidence: 99%
“…Oxygen consumption rates were measured approximately 24 h after the previous feeding and followed procedures modified from [52,53]. Each test subject was gently placed in a 3-L glass respiration chamber containing ultraviolet, light-sterilized, fully aerated fresh water.…”
Section: Oxygen Consumption and Ammonium Excretionmentioning
confidence: 99%
“…It is well understood that marine organisms have varied responses to climate change (Kroeker et al, 2011;Ries et al, 2009), including many marine algae (Harley et al, 2012;Koch et al, 2013;. Climate change will likely obscure a range of cellular to behavioral processes in many marine organisms (Dixson et al, 2010;Elettra et al, 2014;Fabry et al, 2008;Hu et al, 2014;Kelley and Hofmann, 2013). There is a significant difference between the response of calcifiers like coralline algae and non-calcifiers like 'fleshy' macroalgae, the former being most prone to negative effects of ocean acidification (Harley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%